1994
DOI: 10.1159/000236629
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Aspirates and Radiographic Abnormalities in Severe Attacks of Asthma

Abstract: We evaluated the occurrence of abnormalities in paranasal sinus radiographs in acute asthma by taking a radiograph of the sinuses of 110 consecutive patients admitted to a medical ward a total of 149 times for asthma. Maxillary sinus infection was assessed by taking aspirate from radiologically abnormal maxillary sinuses. An abnormal finding in any paranasal sinus was detected on 87% (130 of 149) of admissions and the yield of maxillary aspirate was macroscopically mucous purulent or mucopurulent in 60% (42 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Median age was 40 years (quartiles 29-50), 80% were women, and 20% were current smokers with a mean smoking history of 8.8 pack-years. The median duration of pain before entering the study was six days (quartiles 5-8), and the median duration of pain after entering the study was seven days (quartiles [6][7][8][9][10][11][12][13][14]. The median pain intensity before entering the study was 4 (quartiles 3-4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Median age was 40 years (quartiles 29-50), 80% were women, and 20% were current smokers with a mean smoking history of 8.8 pack-years. The median duration of pain before entering the study was six days (quartiles 5-8), and the median duration of pain after entering the study was seven days (quartiles [6][7][8][9][10][11][12][13][14]. The median pain intensity before entering the study was 4 (quartiles 3-4).…”
Section: Resultsmentioning
confidence: 99%
“…3 A frequent sequela in patients with existing asthma is a worsening of lower airways disease with acute or chronic sinusitis. [4][5][6][7] However, the influence of acute rhinosinusitis on lower airway function in patients without chronic airway diseases or allergy has not been identified in the literature (see www.pubmed.gov).…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of asthma was based on the demonstration o f a revers ible airway obstruction (>20% increase in the FEV, spontaneously or after salbutamol spray) and all subjects met the American Thoracic Society [10] definition o f asthma. Details regarding the patients have been reported previously [8]. Their mean age was 53 years (range 19-83), 57% were women and at least 37% were atopic as judged from two or more positive skin prick test results and a clinical history of atopy.…”
Section: Methodsmentioning
confidence: 99%
“…Rossi et al reported that in 112 adult patients admitted to hospital with acute asthma, 87% had abnormal sinus radiographs. 24 Similarly, a study from the Los Angeles Children's Hospital in 1990 reported that 75% of patients admitted with status asthmaticus had abnormal sinus radiographs. 25 The incidence of abnormal sinus radiographs in these patients is clearly higher than in normal subjects.…”
Section: Imagingmentioning
confidence: 99%